The Influence Of Social Environment And Motivation On Students' Decisions To Become Entrepreneurs: Case Study Of Students Of STIM Budi Bakti - Rita Mardiana; Adrian Adha; Ahmad Juhari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the conditions of students who want to start a business study of the social environment and motivation. This study uses quantitative data where the data is obtained from primary data sources derived from questionnaire data collection. The questionnaire was given to respondents to answer the questions given. The respondents of this study were students who were still active at STIM Budi Bakti. The data collected were analyzed using the SPSS program. The variables in this study consist of independent variables and dependent variables. The Independent Variable (independent variable) consists of: Social Environment (X1) and motivation (X2). While the Dependent Variable (dependent variable) is the Decision to Become an Entrepreneur (Y). The results of this study indicate that the variables of the social environment and motivation have a positive influence on the condition of students in their desire to start a business. The social environment plays a role in influencing the development of individual mindsets and habits in it, while the perception variable has no influence on the interest/desire to become an entrepreneur. Motivation has a simultaneous influence on the student entrepreneurship variable. With the motivation to become an entrepreneur, students become independent (can do many things and can finance their own needs). This shows that students can still have the desire to do business even though their understanding/perception of entrepreneurship is still lacking.